You could simplify this work by factoring "3" out of all four terms, as follows:
3(x^2 + 2x - 3) =3(0) = 0
Hold the 3 for later re-insertion. Focus on "completing the square" of x^2 + 2x - 3.
1. Take the coefficient (2) of x and halve it: 2 divided by 2 is 1
2. Square this result: 1^2 = 1
3. Add this result (1) to x^2 + 2x, holding the "-3" for later:
x^2 +2x
4 Subtract (1) from x^2 + 2x + 1: x^2 + 2x + 1 -3 -1 = 0,
or x^2 + 2x + 1 - 4 = 0
5. Simplify, remembering that x^2 + 2x + 1 is a perfect square:
(x+1)^2 - 4 = 0
We have "completed the square." We can stop here. or, we could solve for x: one way would be to factor the left side:
[(x+1)-2][(x+1)+2]=0 The solutions would then be:
x+1-2=0=> x-1=0, or x=1, and
x+1 +2 = 0 => x+3=0, or x=-3. (you were not asked to do this).
Answer:
10
Step-by-step explanation:
sin30° =
= ![\frac{10}{x}](https://tex.z-dn.net/?f=%5Cfrac%7B10%7D%7Bx%7D)
To find the slope of the above equation, it is easiest to put it into slope-intercept form, y=mx + b, where the variable m represents the slope. To do this, we must isolate the variable y on the left side of the equation by using the reverse order of operations. First, we should subtract 3x from both sides of the equation.
3x + 6y = 9
6y = -3x + 9
Next, we should divide both sides of the equation by 6 to undo the coefficent of 6 on the variable y.
y = -1/2x + 3/2
Therefore, the slope of the line is -1/2 (the coefficient of the variable x in slope-intercept form).
Hope this helps!
Answer:
![\frac{29}{58}](https://tex.z-dn.net/?f=%5Cfrac%7B29%7D%7B58%7D)
Step-by-step explanation:
let x be the numerator of the rational number then 2x is the denominator
original fraction = ![\frac{x}{2x}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B2x%7D)
subtracting 3 from numerator and adding 7 to denominator , gives
=
( cross- multiply )
5(x - 3) = 2(2x + 7) ← distribute parenthesis on both sides )
5x - 15 = 4x + 14 ( subtract 4x from both sides )
x - 15 = 14 ( add 15 to both sides )
x = 29
rational number = ![\frac{29}{58}](https://tex.z-dn.net/?f=%5Cfrac%7B29%7D%7B58%7D)
Answer:
-3
Hope this helps :)
Have a great day !
5INGH
Step-by-step explanation:
![-5\frac{1}{2} - 4\frac{1}{4} +6 \frac{3}{4} = -5\frac{2}{4} - 4\frac{1}{4} +6 \frac{3}{4} = -9\frac{3}{4} +6\frac{3}{4}=-3](https://tex.z-dn.net/?f=-5%5Cfrac%7B1%7D%7B2%7D%20-%204%5Cfrac%7B1%7D%7B4%7D%20%2B6%20%5Cfrac%7B3%7D%7B4%7D%20%3D%20-5%5Cfrac%7B2%7D%7B4%7D%20-%204%5Cfrac%7B1%7D%7B4%7D%20%2B6%20%5Cfrac%7B3%7D%7B4%7D%20%3D%20-9%5Cfrac%7B3%7D%7B4%7D%20%2B6%5Cfrac%7B3%7D%7B4%7D%3D-3)